Natural security : a Darwinian approach to a dangerous world - Sagarin, Rafe; Taylor, Terence (University of California Press, 2008)
Arms races among invertebrates, intelligence gathering by the immune system and alarm calls by marmots are but a few of nature's security strategies that have been tested and modified over billions of years. This provocative book applies lessons from nature to our own toughest security problemsfrom global terrorism to the rise of infectious disease to natural disasters. Written by a truly multidisciplinary group including paleobiologists, anthropologists, psychologists, ecologists, and national security experts, it considers how models and ideas from evolutionary biology can improve national security strategies ranging from risk assessment, security analysis, and public policy to long-term strategic goals.